2012
DOI: 10.1007/s10404-012-0995-6
|View full text |Cite
|
Sign up to set email alerts
|

On the direct employment of dipolar particle interaction in microfluidic systems

Abstract: This review article will summarize recent developments in the employment of dipolar coupled magnetic particle structures. We will discuss the basics of magnetic dipolar particle interaction in static and rotating magnetic fields. In dependence on the magnetic fields employed, agglomerates of different dimensionality may form within the carrier liquid. The stability and formation dynamics of these particle structures will be presented. Furthermore, we will review recent microfluidic applications based on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Petousis et al showed there is a maximum length under which a chain is stable for a given Mn which scales as Mn −1/2 [21]. The unstable regime in which chains break apart and form two-dimensional clusters has only recently been explored [27,28,34]. Here, we present the correlation length of two-dimensional clusters L as a function of Mn.…”
Section: B Viscous Stresses Results In Smaller Clustersmentioning
confidence: 88%
See 1 more Smart Citation
“…Petousis et al showed there is a maximum length under which a chain is stable for a given Mn which scales as Mn −1/2 [21]. The unstable regime in which chains break apart and form two-dimensional clusters has only recently been explored [27,28,34]. Here, we present the correlation length of two-dimensional clusters L as a function of Mn.…”
Section: B Viscous Stresses Results In Smaller Clustersmentioning
confidence: 88%
“…A series of theoretical and experimental studies have shown that the length scales of colloidal chains in magnetic fields scale as Mn −1/2 for 1D chains [21,34]; however, this has not been measured for two-dimenional clusters. The one-dimensional studies were conducted via chains of paramagnetic particles in slowly rotating fields.…”
Section: B Viscous Stresses Results In Smaller Clustersmentioning
confidence: 99%
“…The difference amongst density of the particles and the carrier liquid, as well as the different size of these contaminants causes the liquid to be prone to sedimentation once not in use. When sedimentation occurs, allure due to the remnant magnetization creates redistribution of the [27]. This happening can be inhibited to some huge range using surfactants and substances such as silica gel, xantham gum, stearate and acids.…”
Section: Challengesand Resultsmentioning
confidence: 99%
“…For microspheres that contain superparamagnetic particles (beads), this external constraint can be a homogeneous magnetic field that rotates in plane in a frequency range around 10 Hz. The magnetic field aligns the magnetic moment vectors of the beads, leading to dipolar coupling and attractive forces (see Figure ) . In a rotating magnetic field, this results in the formation of 2D cluster structures that are highly ordered …”
Section: Introductionmentioning
confidence: 99%